Generation and characterization of highly purified canine Schwann cells from spinal nerve dorsal roots as potential new candidates for transplantation strategies. (25th August 2017) - Steffensen, Nicole; Lehmbecker, Annika; Gerhauser, Ingo; Wang, Yimin; Carlson, Regina; Tipold, Andrea; Baumgärtner, Wolfgang; Stein, Veronika M.
Abstract: Schwann cells are promising candidates for transplantation strategies in the central nervous system by promoting axonal regeneration. The dog represents a translational model for human spinal cord injury (SCI) for studies with new repair strategies after intervertebral disk herniation (IVDH). To overcome the necessity for an additional surgical procedure, for the first time a protocol for the isolation and purification of canine Schwann cells from spinal nerve biopsies during standard hemilaminectomy in IVDH‐affected paraplegic dogs for potential transplantation has been developed. Purity was assessed by flow cytometry. The results were compared with biopsies from dogs without SCI. Within 26 ± 4 days, 90.2 ± 8.8% p75 neurotrophin receptor (p75 NTR )‐positive cells were achieved in IVDH dogs. The total cell count in acute/subacute and chronic IVDH (acute/subacute: 6.82 ± 6.36 × 10 6 ; chronic: 2.29 ± 2.00 × 10 6 ) differed significantly ( p  = 0.0120) at the potential time point of transplantation. No differences in culture period and purity were detected between dogs with and without IVDH. Despite the small sample size and the altered environment, the isolation of Schwann cells was successful. Negative influences on isolation and purification due to potential pathological changes at the biopsy site of IVDH‐diseased dogs were ruled out by comparison of Schwann cell pellets from diseased and control dogs. Finally, the functionality of Schwann cells from dogs with IVDH was outlined in co‐culture experiments with canine dorsal root ganglion neurons. In conclusion, nerve root biopsies provide a sufficient number of highly purified and functional Schwann cells within a useful time period for novel therapeutic strategies in dogs with SCI.